PERLINDUNGAN HUKUM BAGI PEMEGANG HAK ATAS TANAH YANG BERSERTIFIKAT GANDA (OVERLAPPING) - Sandra Dikna Apriliani (Fakultas Hukum Universitas Stikubank, 2021)
Land* is* a* necessity* that* is* needed* by* every* Indonesian* citizen.* The* purpose* of* this* study* is* to* find* out* and* analyze* the* resolution* of* legal* disputes* against* holders* of* certificates* of* ownership* (double* certificate).* A sense of wanting to have a subject that will eventually lead to land disputes. One of the problems is the emergence of multiple ownership certificate (overlapping).